2018
DOI: 10.1038/s41598-018-29764-1
|View full text |Cite
|
Sign up to set email alerts
|

A network pharmacology-based approach to analyse potential targets of traditional herbal formulas: An example of Yu Ping Feng decoction

Abstract: Herbal formulas from traditional Chinese medicines (TCMs) have been extensively used in clinics as effective therapies, but it is still a great challenge to demonstrate the scientific basis for their therapeutic effects at the level of molecular biology. By taking a classic herbal formula (Yu Ping Feng decoction, YPF) as an example, this study developed a novel network pharmacology based method to identify its potential therapeutic targets. First, this study constructed a “targets–(pathways)–targets” (TPT) net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 79 publications
3
55
0
Order By: Relevance
“…At the same time, it can predict targets in the networks to maximize damage to the required systems to treat complex diseases [ 25 ]. Excavating underlying information from multistage interactions, especially when dealing with big data, is distinctively advantageous for network analysis [ 26 ]. In addition, since most carcinogens exist within normal cells in the form of mutated proteins, the ideal cancer treatment is aimed at targeting the proteins or interactions essential in cancer cells, but not in normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it can predict targets in the networks to maximize damage to the required systems to treat complex diseases [ 25 ]. Excavating underlying information from multistage interactions, especially when dealing with big data, is distinctively advantageous for network analysis [ 26 ]. In addition, since most carcinogens exist within normal cells in the form of mutated proteins, the ideal cancer treatment is aimed at targeting the proteins or interactions essential in cancer cells, but not in normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…A network module or cluster is defined as a highly interconnected set of nodes that helps discover and reveal hidden biological information within the network [53]. In order to identify the potential mechanism of the 8 key targets, the DHI-UA PPI network was divided into 6 clusters.…”
Section: Module Analysis and Functional Enrichment Analysismentioning
confidence: 99%
“…In recent years, network pharmacology has been proposed as a promising approach for understanding compound formulas [12,13]. Studies have shown that Xuefu Zhuyu decoction and compound Danshen formula have been analyzed by network pharmacology, and the main active compounds in the formulas and the treatment mechanisms have been elucidated [14,15].…”
Section: Introductionmentioning
confidence: 99%